Determination of Phenanthrene and Fluorene by MCM-41-Dispersive Micro-solid Phase Extraction Combined with Gas Chromatography-mass Spectrometry - Mohd Marsin Sanagi (Science Faculty of Chiang Mai University, 2019)
A simple and rapid technique termed MCM-41-dispersive micro-solid phase extraction (MCM-41-D-m-SPE) combined with gas chromatography-mass spectrometry (GC-MS) was utilized for the analysis of polycyclic aromatic hydrocarbons (PAHs) in water samples. Fluorene and phenanthrene were selected as model compounds. Three parameters, namely type of desorption solvent, extraction time and volume of desorption solvent were investigated. In the optimized procedure, MCM-41 (5 mg) was dispersed in water sample (10 mL) in a centrifuge tube and the mixture was agitated vigorously for 2 min followed by centrifugation (5 min) at 3800 rpm. The sedimented adsorbent was dried under nitrogen gas flow and treated with 60 mL of acetone as desorption solvent. 1 mL of final solution was injected into the GC-MS for analysis. This method showed good linearity in the range of 0.3-200.0 mg/L with coefficient of determination (r2) between 0.9973-0.9980. The limits of detections (LODs) were in the range of 0.07-0.16 mg/L. The proposed extraction method provided acceptable recoveries (79.5-107.6 %) with relative standard deviations (RSDs) in the range of 1.7-9.4%. The method was successfully applied to the determination of fluorine and phenanthrene in tap water and lake water samples.